Ionic Liquids and Deep Eutectic Solvents for Application in Pharmaceutics - Branco, Luis Cobra; Santos, Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Dear Colleagues, In recent years, functional coating technology has attracted increased attention due to its effective potential for improved engineered materials. Growing demand for new materials with synergistic properties pushed research toward a new field to obtain innovative and smart coatings with functional capabilities that greatly differ from the conventional ones. In such a context, the expression of "functional coatings" has acquired specific relevance. This Special Issue will assess cutting-edge developments in this research area for the improvement and growth of actual performance, industrial scale-up, and marketability of functional coatings. This Special Issue is useful for researchers who are approaching this application context to improve their knowledge, with the aim of providing valuable scientific support for new research paths concerning functional surface engineering design and tailoring. Prof. Luigi Calabrese, Prof. Edoardo Proverbio Guest Editors